Biodegradable plastics from cassava starch in Thailand - Sriroth, Klanarong; Chollakup, Rungsima; Piyachomkwan, Kuakoon; Oates, Christopher G. (International Center for Tropical Agriculture, 2001)
The paper reviews the role of starch and biodegradable plastics production in Thailand, emphasizing the potential contribution of cassava starch in these products. Types of biodegradable plastics and their manufacturing processes are described. The major types of biodegradable plastics discussed are directly-expanded starch products and various starch-polymer blends (PCL, PLA, PVA and PHA). Research focusing on cassava starch incorporation into biodegradable plastics is summarized.